La parola contaminata dei movimenti non autoritari degli anni settanta - Melandri, Lea (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
This paper shows the function of the word in the process of subjectivation of the body. Starting from Fachinelli’s notion of “contaminated word”, the author investigates how the word has always been an expressive vector for drives, needs and desires. The paper, characterised by an historical and autobiographical perspective, deals with the paths that this “contaminated word” has undertaken in the 70s within self-organized groups: both in the assembly of movements of teachers who fought for a non-authoritarian pedagogy, and in feminist self-consciousness groups. The author also retraces the Italian feminist debate upon the issue of psychism and unconscious as it was brought into the political practices of emancipation.